Mechanism underlying Müller cell pyroptosis and its role in the development of proliferative vitreoretinopathy - Bai, Yue; Xie, Maosong; Zhu, Yihua (Clinics, 2023)
Objectives: To explore the mechanism underlying Müller Cell Pyroptosis (MCP) and its role in the development of Proliferative Vitreoretinopathy (PVR). Method: The expression of pyroptosis-related factors, namely, cysteinyl aspartate-specific proteinase (caspase-1), interleukin (IL)-1β, IL-18, and Gasdermin D (GSDMD), was detected by quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR) and western blotting at the mRNA and protein levels, respectively, in retinal tissues. Müller and spontaneously Arising Retinal Pigment Epithelia (ARPE)-19 primary cells with GSDMD overexpression or knockdown were cultivated. Western blotting was used to detect the levels of the following pyroptosis-related factors in retinal tissues: caspase-1, IL-1β, IL-18, and GSDMD. Through Cell Adhesion (CA) experiments, the changes in ARPE-19 CA in each group were observed. The migration and invasion of ARPE-19 cells were measured using the Transwell assay. The proliferation of ARPE-19 cells was measured with a Cell Counting Kit 8 (CCK-8) assay. Finally, the expression of the cytokines IL-1β and IL-18 in the ARPE-19 cell culture medium was detected using the Enzyme-Linked Immunosorbent Assay (ELISA). Results: Compared with the surrounding normal tissues, the expression of caspase-1, IL-1β, IL-18, and GSDMD at the protein and mRNA levels in the retinal proliferative membrane samples of the patients decreased significantly (p < 0.05). MCP significantly enhanced ARPE-19 CA, migration and invasion, proliferation, and cytokine expression (p < 0.05). Conclusions: MCP can promote the development of PVR lesions.